Evaluation of the effectiveness of a home-based inspiratory muscle training programme in patients with chronic obstructive pulmonary disease using multiple inspiratory muscle tests. Issue 3 (30th January 2016) - Nikoletou, Dimitra; Man, William D.-C.; Mustfa, Naveed; Moore, Julie; Rafferty, Gerrard; Grant, Robert L.; Johnson, Lorna; Moxham, John
Abstract: Purpose : To evaluate the effectiveness of a home-based inspiratory muscle training (IMT) programme using multiple inspiratory muscle tests. Method : Sixty-eight patients (37 M) with moderate to severe chronic obstructive pulmonary disease (COPD) (Mean [SD], FEV1 36.1 [13.6]% pred.; FEV1 /FVC 35.7 [11.2]%) were randomised into an experimental or control group and trained with a threshold loading device at intensity >30% maximum inspiratory pressure (PImax) or <15% PImax, respectively, for 7 weeks. Thirty-nine patients (23 M) completed the study. The following measures were assessed pre- and post-IMT: PImax, sniff inspiratory nasal pressure (SNIP), diaphragm contractility (Pdi, tw), incremental shuttle walk test (ISWT), respiratory muscle endurance (RME), chronic respiratory disease questionnaire (CRDQ), the hospital anxiety and depression scale (HADS) and the SF-36. Between-group changes were assessed using one-way analysis of variance (ANOVA). Results : PImax and perception of well-being improved significantly post-IMT [ p = 0.04 and <0.05 in four domains, respectively]. This was not reflected in SNIP [ p = 0.7], Pdi, tw [ p = 0.8], RME [ p = 0.9] or ISWT [ p = 0.5]. Conclusions : A seven-week, community-based IMT programme, with realistic use of health-care resources, improves PImax and perception of well-being but a different design may be required for improvement in other measures. Multiple tests provide a more comprehensive evaluation of changes in muscle function post-IMT. Implications for Rehabilitation: A seven-week, home-based inspiratory muscle training programme improves maximal inspiratory pressure and perception of well-being in patients with moderate to severe COPD but not sniff nasal inspiratory pressure or diaphragm contractility, respiratory muscle endurance and exercise capacity. Multiple tests are recommended for a more comprehensive assessment of changes in muscle function following inspiratory muscle training programmes. Therapists need to explore different community-based inspiratory muscle training regimes for COPD patients and identify the optimal exercise protocol that is likely to lead to improvements in diaphragm contractility and exercise capacity.